PENGEMBANGAN MODUL IPA INTERAKTIF BERBASIS ETNOSAINS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Muhammad Shohibul Ihsan; Muhammad Zainul Pahmi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2022)
This study aims to produce an interactive ethnoscience-based science module that is valid, practical and effective to improve students' critical thinking skills in science subjects with the subject matter of environmental pollution. This research is included in research and development (Research and Development) referring to the ADDIE development model including the Analysis, Design, Development, Implementation, Evaluation stages. Testing of ethnoscience-based interactive science modules in learning and critical thinking skills tests were conducted on seventh grade students of MTs Nahdlatul Wathan Suela and SMP Nurul Jihad NW Senyiur, NTB. The trial design of this study used the One Group Pretest-Posttest Design. The results showed that the average percentage of the feasibility value of the ethnoscience-based interactive science module from the three validators was 80.6% with very decent criteria, critical thinking ability instrument was 77.7% with proper criteria. The practicality of using an interactive science-based science module based on enscience in the trial got an average score of 75.2% with practical criteria. The ethnoscience-based interactive science module is effective in improving students' critical thinking skills with an average N-gain score of 68 with moderate criteria. These results indicate that the developed interactive science module has valid, practical and effective criteria to improve students' critical thinking skills